2003
DOI: 10.1080/02602930301669
|View full text |Cite
|
Sign up to set email alerts
|

The Other Side of Academic Dishonesty: The relationship between faculty scepticism, gender and strategies for managing student academic dishonesty cases

Abstract: Student academic ethics is a serious concern for colleges and universities. The literature dealing with student academic ethics, however, focuses little attention on the possible connection between organizational characteristics and the efforts made by faculty to deter student academic ethics violations. In this case study analysis of faculty at a medium-sized university in the western USA, we found that the level of faculty institutional confidence is related to the use of formal deterrence strategies. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 25 publications
(17 reference statements)
2
20
0
Order By: Relevance
“…They acknowledged, however, that attitudes are a problematic measure, though many individuals have negative attitudes towards academic dishonesty (they think it is morally wrong and should not be attempted), yet most of them actually engage in this unethical behaviour when the times comes to do so. This is consistent with the study by Simon et al (2003) which suggested that students with favourable attitudes toward academic integrity policies are more likely to report academic dishonesty than those who regard the policies as unfair.…”
Section: Attitude Towards Behavioursupporting
confidence: 81%
“…They acknowledged, however, that attitudes are a problematic measure, though many individuals have negative attitudes towards academic dishonesty (they think it is morally wrong and should not be attempted), yet most of them actually engage in this unethical behaviour when the times comes to do so. This is consistent with the study by Simon et al (2003) which suggested that students with favourable attitudes toward academic integrity policies are more likely to report academic dishonesty than those who regard the policies as unfair.…”
Section: Attitude Towards Behavioursupporting
confidence: 81%
“…Faculty and students who feel connected to the university are probably more likely to feel a sense of responsibility in the maintenance of the organization. The organizational ethics literature abounds with examples that would support this contention (see Simon & Nice, 1997;Simon et al, 2003;DeVries, 2002).…”
Section: Introductionmentioning
confidence: 88%
“…This material should include the rationale for adopting a comprehensive systemic program rather than incremental pieces. Faculty attitudes toward cheating, the enforcement of university policies related to cheating, and the efforts that faculty members make to create a personal connection with students are significant factors that affect the likelihood of students cheating (Simon et al, 2003). Academic integrity encompasses five fundamental values: honesty, trust, fairness, respect, and responsibility (CAI, 2007).…”
Section: Creating a New Modelmentioning
confidence: 99%